THE ASSESSMENT OF KNOWLEDGE AND PRACTICES OF NURSES REGARDING WOUND CARE - ZAFAR , B; FAHEEM , M; SADDIQUE , H; JABEEN , R (Biological and Clinical Sciences Research Journal, 2024)
Proper wound care is critical for patient recovery and infection prevention. Inadequate knowledge and inconsistent practices among nurses can lead to suboptimal patient outcomes, particularly in low- and middle-income countries like Pakistan. Objective: To assess the knowledge and practices of nurses regarding wound care in a tertiary care hospital in Lahore, Pakistan. Methods: A descriptive cross-sectional study was conducted among 133 nurses working in medical wards, surgical wards, and ICUs. Data were collected using a structured questionnaire assessing demographic characteristics, knowledge, and practices related to wound care. Descriptive and inferential statistics were analyzed using SPSS version 26. Results: Among the participants, 73.7% demonstrated good knowledge of wound care, while 26.3% had poor knowledge. However, only 54.1% exhibited good practices, with 45.9% demonstrating suboptimal adherence to wound care protocols. Factors such as insufficient training and high workloads were identified as potential barriers to effective practice. Conclusion: Although nurses possessed good theoretical knowledge of wound care, significant gaps in practice were observed. Targeted training, resource provision, and strict adherence to evidence-based guidelines are essential for improving wound care practices and reducing the incidence of SSIs in Pakistan.